Rationale and design of the Clinical Evaluation of Magnetic Resonance Imaging in Coronary heart disease 2 trial (CE-MARC 2): A prospective, multicenter, randomized trial of diagnostic strategies in suspected coronary heart disease - Ripley, David P. (Am Heart J, 2015)
BACKGROUND: A number of investigative strategies exist for the diagnosis of coronary heart disease (CHD). Despite the widespread availability of noninvasive imaging, invasive angiography is commonly used early in the diagnostic pathway. Consequently, approximately 60% of angiograms reveal no evidence of obstructive coronary disease. Reducing unnecessary angiography has potential financial savings and avoids exposing the patient to unnecessary risk. There are no large-scale comparative effectiveness trials of the different diagnostic strategies recommended in international guidelines and none that have evaluated the safety and efficacy of cardiovascular magnetic resonance. TRIAL DESIGN: CE-MARC 2 is a prospective, multicenter, 3-arm parallel group, randomized controlled trial of patients with suspected CHD (pretest likelihood 10%-90%) requiring further investigation. A total of 1,200 patients will be randomized on a 2:2:1 basis to receive 3.0-T cardiovascular magnetic resonance–guided care, single-photon emission computed tomography–guided care (according to American College of Cardiology/American Heart Association appropriate-use criteria), or National Institute for Health and Care Excellence guidelines–based management. The primary (efficacy) end point is the occurrence of unnecessary angiography as defined by a normal (>0.8) invasive fractional flow reserve. Safety of each strategy will be assessed by 3-year major adverse cardiovascular event rates. Cost-effectiveness and health-related quality-of-life measures will be performed. CONCLUSIONS: The CE-MARC 2 trial will provide comparative efficacy and safety evidence for 3 different strategies of investigating patients with suspected CHD, with the intension of reducing unnecessary invasive angiography rates. Evaluation of these management strategies has the potential to improve patient care, health-related quality of life, and the cost-effectiveness of CHD investigation.